The Hidden Increase in Wage Inequality: Skill-biased and Ability-biased Technological Change - Maren M. Michaelsen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This study provides strong evidence for an increase in wage inequality induced by skillbiased technological change in the UK manufacturing industry between 1991 and 2006. Using individual level data from the BHPS and industry level data from the OECD, wage regressions are estimated which identify the effect of innovative activity on wages - the personal innovation wage premium - for university and less educated workers. Innovative activity is defi ned by R&D expenditure and patent applications to measure innovation input and innovation output, respectively. Using diff erent estimation methods for panel data, such as Fixed effects, Random effects, Mundlak and Hausman-Taylor models, additionally to pooled OLS allows controlling for both industry-specific and individual ability. Using R&D expenditure as a measure for innovative activity additionally provides evidence for ability-biased technological change while patent applications do not support this hypothesis. – – Die Einkommensungleichheit zwischen Hoch- und Geringqualifizierten in Großbritannien scheint im Gegensatz zu den 1970er und 1980er Jahren neuerdings nicht mehr anzusteigen. Diese Studie deckt auf, dass innerhalb des Produktionssektors Einkommensungleichheit durch qualifikationsverzerrten technologischen Fortschritt zwischen 1991 und 2006 durchaus angestiegen ist. Anhand von Personendaten des British Household Panel Survey (BHPS) und Industriedaten der OECD werden Lohnregressionen geschätzt, die den Effekt von Innovationsaktivität auf Löhne für Universitätsabsolventen im Vergleich zu geringer qualifizierten Arbeitnehmern identifizieren. Innovationsaktivität ist einerseits durch Ausgaben für F&E und andererseits durch Patentanmeldungen definiert, um sowohl Innovations-Input, als auch Innovations-Output zu messen. Verschiedene ökonometrische Panel-Schätzmethoden, wie Fixed Effects, Random Effects, Mundlak- und Hausman-Taylor-Modelle, ermöglichen es, für individuelle und industriespezifische Heterogenität zu kontrollieren. Anhand des F&E-Ausgaben-Indikators lässt sich außerdem Evidenz für fähigkeitsverzerrten technologischen Fortschritt finden, während dies anhand des Patentanmeldungen-Indikators nicht möglich ist.
Keywords: I21; J24; J31; O33; 330; Wage inequality; skill-biased technological change; ability-biased technological change; United Kingdom